Effect of pharmacodynamical interaction between nutlin-3a and aspirin in the activation of p53. (7th August 2021) - Awan, Muhammad Suleman; Aslam, Maria; Liaquat, Muwahida; Bhatti, A.I.; Liaquat, Afrose
Highlights: An anti-tumor protein, p-53, is functionally inactivated in most tumors. We have examined the effects of pharmacodynamic interaction between Nutlin-3a and aspirin in cancer patients. The mathematical result shows that p-53 protein gets over-activated and starts suppressing other useful growth cells if a high dose of aspirin along with nutlin-3a is administered in a cancer patient. In order to avoid any harmful effect of such interaction in the activation of p-53 protein, a low dose of aspirin should be administered along with nutlin-3a. Abstract: Background and objective: p53, an anti-tumour protein, is significantly inactivated in most tumours. A small molecule of nutlin-3a is used to activate its function by repressing (Mouse double minute 2 homolog) Mdm2 protein which inhibits its activity. In cancer patients, a high risk of drug-drug interactions (DDIs) is observed owing to their multi-dosing prescriptions, which may lead them to harmful effects. In the presented work, we have aimed to investigate the effect of pharmacodynamical interaction between two anti-cancer drugs, nutlin-3a and aspirin in the activation of p53 protein. Methods: We have adapted control system techniques and designed a Proportional-Integral-Derivative (PID) controller. This controller is used to activate p53 protein. A drug interaction parameter is used to incorporate the effect of both drugs. Extensive simulation is performed using two different doses of aspirin, i.e. a low and a high dose of aspirin. Results: The result shows no harmful effects of pharmacodynamical interaction when a low dose is administered along with nutlin-3a. When a high dose of aspirin is administered it acts as input disturbance and leads to undesirable over-expression of p53 protein. This can further harm other growth cells, thus inducing harmful effects. A comparative analysis is also tabulated with different dosing regimens which shows that a combination of nutlin-3a and a low dose of aspirin provides better results than a high dose of aspirin. Conclusion: Overall, the work provides an insight to the activation of p53 protein in cancer patients under the presence of pharmacodynamical interaction and might contribute to the effective management of cancer patients.